Enhancing Hospitality Service Management and Financial Literacy for Sustainable Tourism Development : Evidence from Malaysia’s Local Destination Operators - Pamungkas, Imang Dapit; Rahayu, Emik; Izza Ulumuddin Ahmad Asshofi; Noviastuti, Nina; Ibrahim, Mohd Hairulnizam (Lembaga Pengembangan Kinerja Dosen, 2025)
In the increasingly competitive tourism landscape, many local operators in Malaysia face challenges in maintaining service quality and managing their businesses sustainably. The objective of this study is to investigate how training in hospitality service management and financial literacy can enhance the long-term sustainability of local tourism businesses. This study aims to examine the impact of hospitality service management and financial literacy training on the business sustainability of local tourism operators. Using a quantitative approach, data were collected from 120 small-scale tourism entrepreneurs in East Malaysia through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that both hospitality service management and financial literacy have a positive and significant effect on business sustainability. Moreover, the integrated implementation of both trainings produces a stronger impact than each intervention individually. These findings support the SERVQUAL Model, Human Capital Theory, and Empowerment Theory, highlighting that knowledge-based capacity building is crucial for improving operational performance and economic resilience in the tourism sector. The study recommends that policymakers and universities adopt integrated training modules that combine service and financial competencies to empower tourism-based microenterprises and foster inclusive, sustainable development.